2011
DOI: 10.1182/blood-2011-05-353102
|View full text |Cite
|
Sign up to set email alerts
|

FcRL4 acts as an adaptive to innate molecular switch dampening BCR signaling and enhancing TLR signaling

Abstract: Ehrhardt et al first described FcRL4 to mark a unique population of memory B cells (MBCs) in human lymphoid tissues near epithelial surfaces that had distinctive functional capabilities. 3 In humans, FcRL4 ϩ MBCs lack CD27, the classic marker for MBCs, and, compared with FcRL4 Ϫ MBCs, express more CD20 and less CD21 and have strongly up-regulated CCR1 and CCR5 that may play a role in their tissue localization. FcRL4 ϩ and FcRL4 Ϫ MBCs have undergone isotype switching and somatic hypermutation to similar levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 38 publications
6
92
0
Order By: Relevance
“…Our observations of enhanced cytokine expression levels in FCRL4 wt transfected Bmem cells after CpG treatment are in agreement with observations of increased CD23 expression in R2G6 cells and primary human B cells in response to TLR9 engagement (24). Investigations into cytokine secretion by B cells have increased over the last decade and led to the recognition of regulatory B cell functions rooted in the modulation of proinflammatory and antiinflammatory cytokine levels.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our observations of enhanced cytokine expression levels in FCRL4 wt transfected Bmem cells after CpG treatment are in agreement with observations of increased CD23 expression in R2G6 cells and primary human B cells in response to TLR9 engagement (24). Investigations into cytokine secretion by B cells have increased over the last decade and led to the recognition of regulatory B cell functions rooted in the modulation of proinflammatory and antiinflammatory cytokine levels.…”
Section: Discussionsupporting
confidence: 90%
“…However, our initial analysis using fusion proteins did not allow us to monitor any effects of the transmembrane region of FCRL4 or of the membrane proximal cysteine 410. Similarly, Sohn et al (24) reported inhibitory activity of FCRL4 in response to Ag receptor ligation in the R2G6 cell line, a subline of Ramos B cells. Expression of FCRL4 in this model system also resulted in significant constitutive tyrosine phosphorylation of FCRL4 and its constitutive association with SHP-1 and SHP-2 phosphatases, and these characteristics might contribute to the observed discrepancy.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Malaria exposure induces atypical MBC to express the inhibitory receptor Fc receptor-like protein (FcRL) 4 (21,26). FcRL4 dampens BCR activation, but enhances TLR9 signaling, favoring a switch from adaptive to innate B cell signaling (51). Moreover, a recent study has shown that tissue-FcRL4 + B cells produce proinflammatory cytokines like IL-6, TNF, and receptor activator for NF-kB ligand in rheumatoid arthritis (52).…”
Section: Discussionmentioning
confidence: 99%